Development of a perioperative venous thromboembolism prophylaxis algorithm for pediatric orthopedic surgical patients. (17th February 2020) - Padhye, Kedar; El-Hawary, Ron; Price, Victoria; Stevens, Sarah; Branchford, Brian; Kulkarni, Ketan
Abstract: Venous thromboembolism (VTE) has been recognized as a rare but potentially serious complication in pediatric orthopedic patients. However, standardized guidelines for screening and management of at-risk patients do not exist. The aim of the study was to develop a VTE prophylaxis screening tool for postoperative orthopedic patients after conducting an institutional needs assessment survey. A needs assessment survey was conducted after institutional ethics board approval. Development of perioperative VTE prophylaxis algorithm for pediatric orthopedic surgical patients was planned after thorough literature review, consultation with national and international experts as well as using a modified nominal and consensus development conference (serial meetings) method for reaching a consensus. NAS as well as discussion with stakeholders indicated support for development of perioperative VTE prophylaxis algorithm for orthopedic patients. Using above methods, a VTE prophylaxis algorithm was developed and implemented at IWK Health Center. The present study involved development of a perioperative VTE prophylaxis algorithm for pediatric orthopedic surgical patients that could be easily and rapidly administered as a point of care assessment tool.